Forensic Histopathology Fundamentals and Perspectives - Dettmeyer, Reinhard B. (Springer International Publishing, 2018)
This second edition, which combines the features of an atlas and a textbook, presents findings in forensic histology, immunohistochemistry, and cytology based on microscopic investigations using different stainings and different antibodies. Questions of quality when working in the field of forensic histology are included as well as scientific perspectives for further research. The principal aim is to provide practitioners with detailed information and guidance on how microscopy can help to clarify the cause of sudden and unexpected death. Therefore additional and particularly rare histopathological findings are presented. Many of the topics will be of interest not only to forensic pathologists but also to general pathologists, whether practitioners or researchers. Examples include the pathology of drug abuse, wound age determination, adverse drug reactions, histopathology of the sudden infant death syndrome, and age determination of myocardial infarction. Both typical and unusual findings are demonstrated with the aid of numerous high-quality color illustrations, and other key literature in forensic histology and immunohistochemistry is highlighted for each topic.